(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Online learning has evolved over the years, becoming increasingly accessible and gaining credibility as a learning medium. Universities are reshaping education on the Web by means of Massive Open Online Courses (MOOC). The learners can access educational content anytime, from anyplace and participatory culture using social networks seems to be the biggest advantage that MOOC has brought to the world of education especially in the higher education arena. MOOC has rapidly developed from a small section of specialist courses to millions of registered users on major online platforms offering hundreds of courses. As MOOC expands, attrition and accreditation is a problem. Though MOOC is expanding very fast, the literature on MOOC research is limited. This paper presents a survey on MOOC providers which aims to capture the state of MOOC, how they evolved and to identify issues and challenges that are important for MOOC providers.